3D Microphysiological System‐Inspired Scalable Vascularized Tissue Constructs for Regenerative Medicine. (26th August 2021) - Bang, Seokyoung; Tahk, Dongha; Choi, Young Hwan; Lee, Somin; Lim, Jungeun; Lee, Seung‐Ryeol; Kim, Byung‐Soo; Kim, Hong Nam; Hwang, Nathaniel S.; Jeon, Noo Li
Abstract: Microphysiological systems (MPSs), based on microfabrication technologies and cell culture, can faithfully recapitulate the complex physiology of various tissues. However, 3D tissues formed using MPS have limitations in size and accessibility; their use in regenerative medicine is, therefore, still challenging. Here, an MPS‐inspired scale‐up vascularized engineered tissue construct that can be used in regenerative medicine is designed. Endothelial cell‐laden hydrogels are sandwiched between two through‐hole membranes. The microhole array in the through‐hole membranes enables the molecular transport across the hydrogel layer, allowing long‐term cell culture. Furthermore, the time‐controlled delamination of through‐hole membranes enables the harvesting of cell‐cultured hydrogel constructs without damaging the capillary network. Importantly, when the tissue constructs are implanted in a mouse ischemic model, they protect against necrosis and promoted functional recovery to a greater extent than implanted cells, hydrogels, and simple gel–cell mixtures. Abstract : Inspired by microphysiological systems, a 3D printed frame sealed with a PEGDA through‐hole porous membrane is developed to fabricate bottom‐up and scalable vascularized tissue construct without damage. The vascularized tissue construct, which recapitulates vasculogenesis in vivo, can be transplanted into the ischemic site for the recovery of blood perfusion and limb salvage.